Effect of Artificial Supplementary Lighting During Autumn and Winter on Leaf Senescence and Development of Winter Fruits of 'Shine Muscat' Grape - Yang FENG; Sihao HUANG; Hengyi XIE; Xiuwen LI; Ling YANG; Jiemei LU; Xuming HUANG (Guangdong nongye kexue, 2023)
【Objective】In recent years, grape industry has developed rapidly in Guangdong Province, which has been a high-profit grape production region where two crops of grape berry can be harvested in a year. However, the short day photoperiod and chilling temperatures in autumn and winter induce systematic leaf senescence, which is unfavorable for over-winter berry development and quality formation in grape. In the study, the effect of artificial supplementary lighting on leaf senescence and berry development in 'Shine Muscat' grape were explored, with an aim to provide technical basis for maintaining leaf function and berry development in winter.【Method】From mid-October, 8-year-old 'Shine Muscat' plants on rootstock of '5BB' were treated with 3 μmol/m2·s red and blue LED light (5∶1) belts, which were placed above the leaves at the fruit cluster node. Light supplementary was carried out from 18:00 to 24:00 until the berries became mature. Changes in chlorophyll index (SPAD value), photosynthetic parameters (Pn) of the leaves at the fruit cluster node and horizontal and vertical diameters of berries were traced, and single berry weight, cluster weight and total soluble solid (TSS) content were collected at mature period.【Result】After 6 weeks of supplementary lighting treatment, leaves at the cluster node in the control plants became yellowing with decreasing SPAD value. While artificial lighting treatment was effective to suppress leaf chlorosis in winter, with significantly lower SPAD decreasing range. After 10 weeks of treatment, leaves at various nodes in supplementary lighting treatment were higher than those at corresponding nodes in the control plants, suggesting that artificial lighting suppressed systematic leaf senescence in winter. The Pn of both lighting treatment and the control plants decreased dramatically from mid-November to late December. However, the decreasing range of Pn was smaller in the lighting treatment. Pn had no significant correlation with stomatal conductance (Gs), but was extremely negatively correlated to mesophyll CO2 concentration (Ci), indicating the reduction of Pn during leaf senescence in winter was mainly caused by non-stomatal limitation. Supplementary lighting treatment maintained Pn via overcoming both stomatal and non-stomatal limitations. the supplementary lighting treatment, significantly increased single berry weight (10.8 g VS 8.8 g), promoted berry horizontal diameter, slightly increased single cluster weight, but significantly reduced total soluble solids (15.0% VS 16.7%).【Conclusion】The results show that supplementary lighting treatment is effective to delay systematic leaf senescence in winter and promote berry growth. It is recommended to use supplementary LED lighting during over-winter grape cultivation in Guangzhou or in regions with similar climate. However, measures should be taken to promote TSS accumulation in the berry.